Evaluation of Reagent-Impregnated Coagulase-Mannitol Test Strip for Speciation of Staphylococci - Washington, John A. (1970)
A new coagulase-mannitol reagent-impregnated strip test has been evaluated with 322 Micrococcaceae. Mannitol fermentation was determined accurately by this test; however, the coagulase reaction was difficult to interpret and was subject to significant error.